2022
DOI: 10.1002/cam4.5185
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐lymphocyte ratio in relation to risk of hepatocellular carcinoma in patients with non‐alcoholic fatty liver disease

Abstract: Background Blood neutrophil to lymphocyte ratio (NLR) or lymphocyte count may be important markers for immune function. Previous work has shown higher NLR was associated with higher risk of hepatitis B‐related hepatocellular carcinoma (HCC). However, studies in non‐alcoholic fatty liver disease (NAFLD) patients are lacking. Methods Utilizing the University of Pittsburgh Medical Center (UPMC) electronic health records, we created a retrospective cohort of 27,834 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
2
4
0
Order By: Relevance
“…The NLR, frequently used to assess inflammatory disorders, measures the absolute quantity of neutrophils in lymphocytes [30]. Our findings are in concordance with the evidence from a recent study by Thomas et al [31], who showed that patients with NAFLD with higher NLR counts have a greater chance of developing HCC.…”
Section: Discussionsupporting
confidence: 92%
“…The NLR, frequently used to assess inflammatory disorders, measures the absolute quantity of neutrophils in lymphocytes [30]. Our findings are in concordance with the evidence from a recent study by Thomas et al [31], who showed that patients with NAFLD with higher NLR counts have a greater chance of developing HCC.…”
Section: Discussionsupporting
confidence: 92%
“…The pathogenesis of HCC is closely related to immune status and inflammatory response ( 36 ). Our and other studies have reported that a higher NLR and lower lymphocyte count are associated with a significantly higher risk of HCC in patients with hepatitis-B related cirrhosis and non-alcoholic fatty liver disease ( 37 , 38 ). The immune system plays an important role in immune surveillance and controls tumor growth effects ( 39 ).…”
Section: Discussionsupporting
confidence: 55%
“…In the current review, one study was found linking NLR and absolute lymphocyte count to the prediction of HCC. NLR ≥ 3.09 predicted HCC development (HR: 1.43 (95% CI: 1.01–2.03), Table 2 ), whereas an absolute lymphocyte count ≥ 2.15 predicted lower HCC incidence (HR: 0.64 (95% CI: 0.43–0.94), Table 2 ) over 5.5 years follow-up [ 70 ]. Importantly, the authors of the study note that the NLR and lymphocyte count-associated risk of HCC development was independent of advanced fibrosis, as patients with mild fibrosis had the same risk to develop HCC as those with advanced fibrosis, provided their NLR and absolute lymphocyte count values were higher than the designated threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the authors of the study note that the NLR and lymphocyte count-associated risk of HCC development was independent of advanced fibrosis, as patients with mild fibrosis had the same risk to develop HCC as those with advanced fibrosis, provided their NLR and absolute lymphocyte count values were higher than the designated threshold. For this reason, the authors recommend using NLR and absolute lymphocyte counts as early markers of HCC rather than biomarkers for unidentified cirrhosis [ 70 ]. NRL and absolute lymphocyte count represent potentially interesting treatment monitoring biomarkers, as they reflect changes in immune cell dynamics that can be fluctuating according to the intensity of the immune response itself.…”
Section: Resultsmentioning
confidence: 99%